A priming role of local estrogen on exogenous estrogen-mediated synaptic plasticity and neuroprotection - Siriporn Chamniansawat (2018)
The localization of estrogen (E2) has been clearly shown in hippocampus, called local hippocampal E2. It enhanced neuronal synaptic plasticity and protected neuron form cerebral ischemia, similar to those effects of exogenous E2. However, the interactive function of hippocampal and exogenous E2 on synaptic plasticity activation and neuroprotection is still elusive. By using hippocampal H19-7 cells, we demonstrated the local hippocampal E2 that totally suppressed by aromatase inhibitor anastrozole. Anastrozole also suppressed estrogen receptor (ER)β, but not ERα, expression. Specific agonist of ERα (PPT) and ERβ (DPN) restored ERβ expression in anastrozole-treated cells. In combinatorial treatment with anastrozole and phosphoinositide kinase-3 (PI-3K) signaling inhibitor wortmannin, PPT could not improve hippocampal ERβ expression. On the other hand, DPN induced basal ERβ translocalization into nucleus of anastrozole-treated cells. Exogenous E2 increased synaptic plasticity markers expression in H19-7 cells. However, exogenous E2 could not enhance synaptic plasticity in anastrozoletreated group. Exogenous E2 also increased cell viability and B-cell lymphoma 2 (Bcl2) expression in H 2 O 2 -treated cells. In combined treatment of anastrozole and H 2 O 2 , exogenous E2 failed to enhance cell viability and Bcl2 expression in hippocampal H19-7 cells. Our results provided the evidence of the priming role of local hippocampal E2 on exogenous E2-enhanced synaptic plasticity and viability of hippocampal neurons. © 2012 by the Korean Society for Biochemistry and Molecular Biology.